Effect of Spinetoram Stress on Midgut Detoxification Enzyme and Gene Expression of Apis cerana cerana Fabricius - Lin Chen; Tianjun He; Linglong Ding; Xinyan Lan; Jiahao Sun; Xiaoheng Xu; Huafen Wu; Dayun Zhou; Zhichu Huang; Tianxing Zhou; Xiaoling Su; Limin Chen (Insects)
This study aimed to evaluate the impact of Spinetoram (SPI) on the midgut of Apis cerana cerana Fabricius pupae, emphasizing detoxifying enzyme activity, gene expression, and morphological alterations. Pupae were subjected to SPI at LC20 and LC50 concentrations, and the midgut was evaluated using morphological assessment, detoxifying enzyme assays, and transcriptome analysis utilizing gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Transcriptome analysis revealed 32 differentially expressed genes (DEGs) that were common to both the LC20 vs. control (CK) and LC50 vs. CK comparisons, along with 24 DEGs unique to the LC20 vs. CK comparison and 76 DEGs unique to the LC50 vs. CK comparison. KEGG pathway analysis indicated the substantial enrichment of pathways associated with drug metabolism, xenobiotic metabolism, and amino acid metabolism, implying disruptions in detoxification mechanisms and broader metabolic imbalances resulting from SPI exposure. Morphological analysis showed a normal midgut structure in the control group, while significant damage was observed in the LC20 group, and severe degeneration was observed in the LC50 group. Detoxification enzyme assays revealed that the activities of cytochrome P450, glutathione S-transferase, and carboxylesterase significantly increased at LC20 (p < 0.05), indicating an initial induction of detoxification responses; however, they declined at LC50, suggesting enzyme inhibition or midgut damage. The activity of acetylcholinesterase markedly diminished at both LC20 and LC50 (p < 0.05), with a more substantial decline observed at LC50, suggesting possible neurotoxicity. These findings indicate that SPI exposure causes substantial alterations in midgut morphology, detoxifying enzyme activity, and gene expression in Apis cerana cerana Fabricius pupae, underscoring the insecticide’s detrimental impact on honey bee health.